"Lead by Example": A Phenomenological Study of School Counselor–Principal Team Experiences With LGBT Students. (January 2017) - Beck, Matthew J.
This phenomenological study explored the collaborative experiences between school counselors and principals in their work with lesbian, gay, bisexual, and transgender (LGBT) students. The study data revealed four overarching themes: (a) learning through storytelling, (b) leading by example, (c) creating intentional partnerships, and (d) pushing the system. This article includes implications for future research and school counselor practice regarding how school counselors and principals can forge a strong, intentional relationship toward effective advocacy for LGBT youth.